A study on factors affecting academic performance among Universiti Malaysia Sabah students - Sarroginee Subramanim (2015)
This study is mainly about the factors affecting student's academic performance in Universiti Malaysia Sabah. The objectives of this find out are to study the trend of attendance among students taking Statistic Economy subject to examine the relationship between student attendance and academic performance and to determine the effect of other demographic factors on academic performance. Data collection by means of distribution of questionnaires to students enrolled in Statistic Economy subject. There are 115 students who have participated in this survey. There are few tests used in this research to analyze the data collected. Those are descriptive analysis, normality test, Independent-groups t-tests, Kruskal Wallis test, Spearman rank correlation coefficient test and multiple regression analysis. The result shows the effects of attendance, family background, entry qualification, hours of study and gender on student's academic performance. Student's academic achievement has relation with tutorial attendance and student's entry qualification. Other than that, there is no correlation between student's academic performance and other demographic factors like family background, hours of study and gender. Based on the multiple regression analysis, it illustrates that STPM leavers (ßSTPM = 21.19) and Foundation leavers (ßFoundation = 11.67) are the significant factors affecting academic performance at 5% level of Significance.